ANALISIS KESULITAN BELAJAR SISWA PADA PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM KELAS III DI MI MA’HAD ISLAMY PALEMBANG - Fizalika; Maryamah; Muhamad Afandi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the learning difficulties experienced by students in Islamic Cultural History lessons in grade III MI Ma'had Islamy Palembang. The purpose of this study is to determine students' learning difficulties, the factors causing them, and the teachers' efforts to overcome them. The method used is a qualitative method with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation. The study subjects consisted of Islamic Cultural History teachers and grade III MI Ma'had Islamy Palembang students. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. Data validity techniques used source triangulation and technical triangulation. The results of the study showed that students had difficulty understanding the learning material, lacked focus during learning, easily felt bored, and had not achieved learning targets optimally. Factors causing learning difficulties consisted of internal and external factors. Internal factors include physical health conditions, psychological conditions, learning motivation, and low student concentration. While external factors include teacher learning methods, lack of use of learning media and technology, and a less conducive learning environment. Teachers' efforts to address learning difficulties include identification, diagnosis, provision of assistance and guidance, implementation of interventions, evaluation, and follow-up in the form of remedial and additional guidance. Based on the study's findings, it can be concluded that student learning difficulties are influenced by various factors, necessitating planned efforts and the use of more engaging learning methods to facilitate student understanding of the material. The results of this study are expected to serve as evaluation material for teachers in improving the quality of Islamic Cultural History instruction in elementary schools.